Hubungan Integrasi Nilai-Nilai Islam Dengan Hasil Belajar Mahasiswa PGSD Pendidikan Jasmani - Amelia Putri, Nadia; Rizki Alfarizi, Bayu; Nurhalim, Ikhsan; Akbar Subagja, Nadzar; Wahyudi, Arbiansyah; Parhan, Muhamad (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Education plays a crucial role in fostering the advancement of a nation. The demand for highly qualified human resources with extensive insights encompasses not only general knowledge but also a solid moral foundation. This study aims to explore the relationship between the integration of Islamic values and the academic performance of students in the PGSD Penjas programme. In the current era of rapid globalisation and digitalisation, character education has emerged as a significant issue that continues to be advocated within the educational system in Indonesia. This research employs a quantitative method with a correlational design, targeting the entire population of PGSD Penjas students. The research sample consists of 52 students, selected using purposive sampling techniques based on the following criteria: 1) Active PGSD Penjas students, 2) Those who have completed the PAI (Islamic Religious Education) course, and 3) Students who are at least in their third semester. The results indicate a significant relationship between the integration of Islamic values and the academic performance of PGSD Penjas students, with a calculated r value of 0.297. This value suggests that the relationship between the two variables is at a low level. These findings imply that, in addition to the integration of Islamic values, other factors also influence students' academic performance, such as teaching methods, learning motivation, and the academic environment. Therefore, further research is necessary to identify these factors in order to enhance the learning process sustainably.